COMMUNICATION BASED ON LOCAL WISDOMS TO CREATE TWO–WAY SYMMETRICAL PUBLIC RELATIONS - Hasmah Zainuddin; Aizirman Djusan (The Indonesian Journal of Communication Studies, 2015)
Most of Public Relations research adopt Grunig’s model which divided Public Relations practices into four types; press agentry, public information, two-way asymmetrical, and two-way symmetrical model. The history shown the practices has been stressed on the types of press agentry and public information at the beginning until it emerged the two-way communication which is considered to be more effective. Cultural approach on Public Relations has been deliberated since 1992 through Hofstede’s values and Excellence Theory of communication. Culture as an environment for Public Relations affects and is affected by Public Relations practices. Some studies on the effect of culture on Public Relations practices are found in specific countries. This paper convinces the chances of local wisdoms as a part of culture to create symmetrical Public Relations. Local wisdoms acquiredand passed downfrom generation to generationcan be observedthrough cultural approach which includes knowledge, belief, art, morals, law, custom and any other capabilities and habits of human as a member of society. The methodology used is literature reviews and exposure to the practices in some cases in Indonesia. It is expected that this study can motivate scholar to do empirical evidence and build a database of more types of local wisdoms in order to help practitioners (in corporations, governments and non-profits) reach out to their relevant publics.